Survai Pemetaan Tanah Di Kecamatan Teluk Meranti, Pelalawan - Besri Nasrul (Universitas Riau, 2007)
To optimize the utilization of the soils, especially in the wetlands, precise and comprehensive understanding of soil characteristic is needed to support agricultural works. The study was conducted in the Teluk Meranti District, Pelalawan for five months. The field survey was carried out on 1:50.000 scale map which was used for mapping, classifying, describing morphological, physical, and chemical soil properties. The soil classification systems applied to this study were soil taxonomy until family categories. The result of study indicated that areas occupied by six soil mapping units were: sapric haplohemist on 42.173 Ha areas (11%); typic haplohemist on 111.520 Ha areas (29%); typic haplosaprist on 212.486 Ha areas (54%); typic endoquents on 14.310 Ha areas (3%); sulfic endoaquepts on 4.297 Ha areas (1%); humic endoaquepts on 5.235 Ha areas (1%). Key words: soil survey, soil mapping, soil classification, Pelalawan